WI2020 Zentrale Tracks 2020
DOI: 10.30844/wi_2020_a6-poser
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Teamwork: Consideration of Teamwork Concepts to Reach Naturalistic Interaction between Humans and Conversational Agents

Abstract: Hybrid teamwork between humans and conversational agents (CA) is a promising approach to augment humans' thinking and problem solving during task work. To realize a natural interaction, it is inevitable to consider research insights from human-centric disciplines for the design of CAs, as human team members have underlying assumptions regarding team work that need to be addressed to achieve valuable outcomes in hybrid teamwork settings. In this paper, we conducted a systematic literature review to consolidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Seeber et al (2020) note that "Machine teammates could be training for specific collaboration processes, such as coordination, knowledge sharing, or evaluation …which might spark changes in creativity, groupthink, or problem solving" (p. 6). This expansion of technology's role in teams (i.e., as active teammates) raises a number of very interesting research questions around how to apply insights from the organizational science literature to these kinds of hybrid teams (Poser & Bittner, 2020). To select just two: (1) How do team emergent states such as cohesion, efficacy, and trust form among human and technology-based teammates, and (2) How do humans weigh the contributions of technology in the transition and action phases of hybrid team performance episodes?…”
Section: Technological Inputsmentioning
confidence: 99%
“…Seeber et al (2020) note that "Machine teammates could be training for specific collaboration processes, such as coordination, knowledge sharing, or evaluation …which might spark changes in creativity, groupthink, or problem solving" (p. 6). This expansion of technology's role in teams (i.e., as active teammates) raises a number of very interesting research questions around how to apply insights from the organizational science literature to these kinds of hybrid teams (Poser & Bittner, 2020). To select just two: (1) How do team emergent states such as cohesion, efficacy, and trust form among human and technology-based teammates, and (2) How do humans weigh the contributions of technology in the transition and action phases of hybrid team performance episodes?…”
Section: Technological Inputsmentioning
confidence: 99%
“…In addition, research in this stream also investigates how new forms of human-computer interactions with conversational interfaces using natural language, either written or spoken, could evolve (Poser & Bittner, 2020). Nowadays, conversational interfaces such as Apple's Siri, Microsoft's Cortana, Amazon's Alexa, or Google's Assistant are ubiquitous, and they are used in several areas, such as customer service, health care or education (Janssen et al, 2020).…”
Section: Design Of Hybrid Intelligence Systemsmentioning
confidence: 99%
“…For example, Bittner et al [13] developed a taxonomy of design option combinations for Conversational Agents (CAs, a specific form of AI) in collaborative work and distinguished between AI as facilitator, peer or expert in various collaboration settings [17]. In addition, Poser and Bittner [18] conducted a systematic literature review and found that CAs are mainly purposed for task-related activities and not for relationship-related activities in teamwork. As a specific example in collaborative writing, Wiethof et al [19] investigated the UI design principles for CAs that encouraged optimal user acceptance.…”
Section: Introductionmentioning
confidence: 99%